Navigating Digital Selves: Gendered Consumption and Media Work Among Millennial Women in Makassar - Irwan (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study aims to examine how social media content influences consumer choices, particularly regarding the behavior of visiting cafés and restaurants not solely for eating and drinking, and how digital content fulfills the sociological needs of consumers. The research focuses on female journalists who are members of the Ruang Jurnalis Perempuan (RJP) community in Makassar City. The findings reveal that social media platforms such as TikTok, Instagram, and Facebook serve as primary references when selecting comfortable and trendy workspaces. Consumer choices are influenced not only by the menu but also by comfort, supporting facilities, and the ambiance of the location. Furthermore, cafés function as alternative social spaces—venues for networking, idea sharing, and creating collaborative opportunities. These findings highlight a shift in the meaning of consumption and public space, as well as a transformation in women’s work lifestyles in the digital era